Building capacity on Policy Analysis Tools in Colombia #NPSinitiative - Castillo, Johana M.; Gonzalez Rodriguez, Carlos Eduardo (CGIAR System Organization, 2023)
As part of the national policy and strategy initiative, the Alliance of Bioversity and CIAT, in collaboration with the International Food Policy Research Institute (IFPRI), is deploying strategies to promote and strengthen the integration of policy and investment tools within the Colombian context. As part of this effort, the “Policy Analysis Tools using General Equilibrium Models for Colombia” course was held, a three-day in-person course conducted in collaboration with the Agri-Food Systems Research Center at the University of Los Andes.